Convolution Properties of Certain Classes of Analytic Functions Defined by Jackson q-Derivative - Abdel Moneim Y. Lashin; Badriah Maeed Algethami; Abeer O. Badghaish (Mathematics, 2021)
In this paper, the Jackson q-derivative is used to investigate two classes of analytic functions in the open unit disc. The coefficient conditions and inclusion properties of the functions in these classes are established by convolution methods.